Study, conservation and exhibition of human remains: the need of a bioethical perspective - Licata, Marta; Bonsignore, Alessandro; Boano, Rosa; Monza, Francesca; Fulcheri, Ezio; Ciliberti, Rosagemma (Acta Biomedica Atenei Parmensis, 2020)
Today, the recovery, study and exposition of archaeological human remains are subjected to new discussions. Human remains preserve a clear record of past life to later generations. These remains, even if dated hundreds or thousands of years ago, maintain their human dignity and force the community to reflect on the ethical issues related to their analysis, curation and display.Such a topic stimulate a continuous dialogue between the different actors of the bioarchaeological/osteoarchaeological/anthropological (physical and forensic) field: archaeologists, anthropologists, bioethicists, museum curators and other figures in order to give voice to a broad range of approaches and identify shared paths on the management of human remains that respect human dignity and different cultural values of community.As a “culturally sensitive material”, human remains collections must be acquired and handled with respect regardless of their age and legitimacy of provenance.The opening up to disciplines quite far from the expertize of museum curators is an essential prerequisite to increase awareness towards ethical issues and to develop guidelines that take into account the dignity of the person and the cultural values of community to whom human remains belonged.Accordingly, the authors stimulate the increase of the discussion and try to identify solutions sensitive to the issue.